PENGARUH UKURAN PERUSAHAAN, SALES GROWTH, DAN LEVERAGE TERHADAP TAX AVOIDANCE DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING (STUDI KASUS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022) - Hardini Ariningrum; Renia Mersanda; Eka Sariningsih; Ritali Evi Mudrikah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the influence of sales growth, company size, and leverage on tax avoidance, with profitability as a moderating variable. The focus is on manufacturing companies listed on the IDX from 2020 to 2022, driven by rampant tax evasion practices that hamper state revenues. A quantitative approach was applied using secondary data obtained from annual financial reports. A total of 61 samples were obtained through purposive sampling. Data analysis included testing classical assumptions and multiple linear regression, using MRA through IBM SPSS Statistics. The findings show that company size has a significant negative impact on tax avoidance, due to stricter public scrutiny of larger companies. Conversely, sales growth and leverage have a positive and significant impact. Profitability moderates the effects of company size and leverage, but not sales growth. Simultaneously, the independent variables explain 46.8% of the variation in tax avoidance.